Development of Grave Tracker System - Mohamad Rozi, Muhamad Norsalahudin; Mohamad, Radiah (Applied Information Technology And Computer Science, 2023)
Grave Tracker is a web-based system that works to track and record the information about the grave at Kg TengluLaut, Mersing Johor. The proposed system aims to improve the weakness of the existing method which is the use of books as a medium to record information about graves. The prototype model was used to develop this proposed project. The development of this proposed system is by using the MySQL database. The programming languages used are Hypertext Preprocessor (PHP), Hypertext Mark-up Language (HTML) and using Laravel as Framework. Generally, the Grave Tracker was built to increase the effectiveness and efficiency in managing the collection of data or information by the grave management at Tanah Perkuburan Kg TengluLaut.